2023
DOI: 10.1002/jad.12254
|View full text |Cite
|
Sign up to set email alerts
|

Friendship attachment style, intolerance of uncertainty, and psychological distress among unaccompanied immigrant minors in times of COVID‐19

Chiara Ceccon,
Ughetta Moscardino

Abstract: IntroductionThis cross‐sectional study used a convergent parallel mixed‐method design to investigate friendship attachment style, intolerance of uncertainty, and psychological distress among unaccompanied immigrant minors (UIMs) during the second wave of the COVID‐19 pandemic in Italy.MethodParticipants were 80 male UIMs (Mage = 17 years, standard deviation = 0.84) hosted in residential care communities. Individual interviews comprising questionnaires and open‐ended questions assessed the constructs of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
0
1
Order By: Relevance
“…Compared to previous studies ( 74 , 75 ), our study found that IU levels were higher during students’ preparation for the art college entrance examination than other periods. In China, parents tend to hold high expectations with regards to education ( 1 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Compared to previous studies ( 74 , 75 ), our study found that IU levels were higher during students’ preparation for the art college entrance examination than other periods. In China, parents tend to hold high expectations with regards to education ( 1 ).…”
Section: Discussioncontrasting
confidence: 99%